Schnitzler Syndrome: An Under-Recognised Cause of Pyrexia of Unknown Origin - Dennis Tin Ho Chan; Ling Yin Ho (Journal of Clinical Rheumatology and Immunology, 2025)
Schnitzler syndrome is a rare adult-onset autoinflammatory disease characterised by urticarial rash, monoclonal gammopathy, and systemic inflammation. We present the first reported case in Hong Kong, involving a 37-year-old female with a prolonged diagnostic journey of nearly a decade after initially presenting with pyrexia of unknown origin. Extensive investigations ruled out other causes, and the diagnosis was made using the Strasbourg diagnostic criteria for Schnitzler syndrome. Treatment with canakinumab, an interleukin (IL)-1[Formula: see text] inhibitor, resulted in rapid resolution of symptoms. This case highlights the importance of early recognition and timely diagnosis to improve patient outcomes in this rare condition.